ETHNOBOTANICAL SURVEY OF THE MURONG TRIBE INHABITING THE CHITTAGONG HILL TRACTS REGION OF BANGLADESH - Rana, Md. M.; Shahadat, Md.; Hanif, H. A.; Rahmatullah, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The Murongs are a tribal community inhabiting the Chittagong Hill Tracts region of Bangladesh. They rely on their own traditional healers, who are experts in medicinal plants for cure of various ailments. An ethnobotanical survey was carried out amongst the Murong tribe to identify their medicinal plants. Interviews of traditional healers were conducted using a semi-structured questionnaire as to plant or plant parts used as well as medicinal preparation, diseases, dosage, and side-effects, if any. Plants identified by Murong healers were photographed and herbarium specimens were sent to Bangladesh National Herbarium for complete identification. A total of 50 plants were collected out of which 45 plants belonged to 34 families and five plants remain unidentified. The various ailments claimed to be cured by plant or plant parts include body, joint and rheumatic pains, coughs, colds, tonsillitis, bronchitis, sore throat, fevers, vomiting, tooth problem, edema, abscesses, ear infections, wounds, poisonous insect bites, bone fractures, acidity, diarrhea, dysentery, diabetes, cholera, tetanus, intestinal worms, headache, conjunctivitis, urinary tract disorders, leucorrhea, ringworms, eczema, scabies, fungal infections, gonorrhea, impotency, hepatic disorders, malaria, insanity, and diabetes. Our preliminary data suggest that a number of medicinal plants of the Murong are unique and needs to be scientifically studied for isolation of pharmacologically active constituents or lead compounds.